The effect of feed pH and in-situ pH adjustment on the behaviour of an anaerobic sequencing batch reactor treating synthetic winery wastewater - Smit, Jason (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.